Meta-analysis of social cognition in mild cognitive impairment - Bora, Emre; Yener, Görsev G. (Sage Publications Inc, 2455 Teller Rd, Thousand Oaks, Ca 91320 USA, 2017)
Social cognitive abilities are impaired in Alzheimer disease and other dementias. Recent studies suggested that social cognitive abilities might be also impaired in mild cognitive impairment (MCI). Current meta-analysis aimed to summarize available evidence for deficits in theory of mind (ToM) and emotion recognition in MCI. In this meta-analysis of 17 studies, facial emotion recognition and ToM performances of 513 individuals with MCI and 693 healthy controls were compared. Mild cognitive impairment was associated with significant impairments falling in the medium effect sizes range in ToM (d = 0.63) and facial emotion recognition (d = 0.58). Among individual emotions, recognition of fear and sadness were particularly impaired. There were no significant between-group differences in recognition of disgust, happiness, and surprise. Social cognitive deficits were more severe in multidomain MCI. There is a need for longitudinal studies investigating the potential role of social cognitive impairment in predicting conversion to dementia.
Keywords: mild cognitive impairment; emotion recognition; social cognition; theory of mind; Variant Frontotemporal Dementia; Facial Emotion Recognition; Alzheimers-Disease; Behavioral-Variant; Mind; Abilities; Subtypes; Deficit; MCI